2022
DOI: 10.1111/josi.12548
|View full text |Cite
|
Sign up to set email alerts
|

Integration or isolation: Social identity threat relates to immigrant students’ sense of belonging and social approach motivation in the academic context

Abstract: Stigmatized individuals often feel threatened by negative stereotypes about their group. Previous research showed that concerns about being negatively stereotyped (i.e., social identity threat) have detrimental effects on performance in the stereotyped domain. Little research has focused on interpersonal consequences of negative stereotypes, despite their essential role for integration of stigmatized groups like immigrants. The current workThis is an open access article under the terms of the Creative Commons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Doyle and Molix (2014) focused on physiological and psychological pathways for the adverse impacts of discrimination on relationship quality and showed that the effect was mediated by increased emotion dysregulation and chronic inflammation. Further psychological pathways may include decreased trust (Zhang et al, 2020), a reduced sense of belonging (Froehlich et al, 2023), or loss of control that can lead to aggression and controlling behavior (Kazmierski et al, 2023; Petsnik & Vorauer, 2023). Furthermore, discrimination can manifest within relationships, for instance in the form of friendly teasing, making discrimination more ambiguous and thus more challenging to cope with (Douglass et al, 2016; Yampolsky et al, 2023).…”
Section: Levels Of Discriminationmentioning
confidence: 99%
“…Doyle and Molix (2014) focused on physiological and psychological pathways for the adverse impacts of discrimination on relationship quality and showed that the effect was mediated by increased emotion dysregulation and chronic inflammation. Further psychological pathways may include decreased trust (Zhang et al, 2020), a reduced sense of belonging (Froehlich et al, 2023), or loss of control that can lead to aggression and controlling behavior (Kazmierski et al, 2023; Petsnik & Vorauer, 2023). Furthermore, discrimination can manifest within relationships, for instance in the form of friendly teasing, making discrimination more ambiguous and thus more challenging to cope with (Douglass et al, 2016; Yampolsky et al, 2023).…”
Section: Levels Of Discriminationmentioning
confidence: 99%
“…On the other hand, different psychological mechanisms partly explain the association between low socioeconomic status and a weaker sense of belonging. Environmental cues as the awareness of the numerical underrepresentation of students of lower socioeconomic status or acknowledging negative class stereotypes can lead individuals from lower economic backgrounds to entertain the notion that people like them do not fit in evoking sentiments of uncertainty regarding belonging (Froehlich et al, 2023; Walton & Cohen, 2007, 2011). These belonging concerns might, in turn, lead students of low socioeconomic status to make extremely negative interpretations of the typical difficulties (e.g., academic obstacles) that affect everyone, starting a vicious circle that harms their well-being and academic performance (Walton & Cohen, 2011).…”
Section: Socioeconomic Status Sense Of Belonging and Academic Achieve...mentioning
confidence: 99%
“…Perceived similarity is a precursor to liking and a sense of connection with others (Hampton et al, 2018; McPherson et al, 2001), so when immigrants cannot identity with their host country or host country nationals, they lose the motivation to interact with their native counterparts (Di Saint Pierre et al, 2015; Froehlich et al, 2022). Of course, it is not surprising that individuals prefer to socialize with members of their own ingroup (Mehra et al, 1998) but a preference for non-native relationships can limit immigrants’ language proficiency which is vital for their social and cultural integration (De Vroome et al, 2014).…”
Section: Acculturation and Immigrants’ Sense Of Belongingmentioning
confidence: 99%